(3GdNOeI GdeLJeYjI cHOjd ddYbhHGJ GdSGdHI ddMQjI bUjQI GdeOI (B:s " (3OQGSI ebGQfI (B" / s - (3SdjeGf Ydj SdjeGf CMeO GdRjhOjs; (3YeQ eMeO SGdes; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI(B:s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2023)
(3XgQJ GdLQjeI eY hLhO GdHTQjI , hMJi jhefG GdQGgf de JfJgj GdLQjeI aj Cj MVGQI , Ch eLJeY Ydi hLg GdCQV , acGfJ fTCJ GdYbhHI dGQJHGWgG HGdXGgQI GdELQGejI hGdJj EQJHW hLhOgG HhLhO GdeLJeY GdHTQj PGJg , aGdYbhHI bOjeI bOe GdeLJeY GdEfSGfj HGYJHGQgG JeKd QO GdaYd , Cj JeKd ERGA ef NGda bhGYO GdSdhc GdGLJeGYj(B. (3hbO GJNPJ GdYbhHI efP GdbOe UhQkG eJHGjfI , JWhQJ eY JWhQ GdLeGYI GdEfSGfjI, hJWhQ eYfi GdSdWI aj GdLeGYI , hcPdc JWhQ GdefXhQ GdOjfj aj GdeLJeY , hGfJbGd GdeLJeYGJ ef eQMdI GdRQGYI Edi eQMdI GdUfGYI , hNdGd gPG GdeQGMd GdRefjI fTCJ hJWhQJ GdYOjO ef GdeOGQS GdacQjI GdJj JDSS dacQI GdMb aj GdYbGH , GdCeQ GdPj jYJHQ HOGjI GdfTCI GdMbjbjI dacQI GdYbGH aj GdYUhQ GdMOjKI(B. (3hfXQkG dchf GdacQ GdbGfhfj Ph WHjYI eJWhQI heJLOOI JhGcH JWhQGJ GdEfSGf ef ReGf Edi BNQ, abO XgQJ GdYbhHGJ GdSGdHI ddMQjI , hef Ke GfTCJ GdSLhf djS abW ecGf dJfajP Jdc GdYbhHGJ , Hd dJQLeI adSaI, hCgOGa , hhXjaI GdYbhHI Edi hGbY JfajPj edehS ef NdGd JWHjb GdHQGeL GdEUdGMjI hGdJCgjdjI GdeJeKdI HJgPjH Sdhc GdLGfj, hJKbjag egfjkG , hOjfjkG , hJCgjdg faSjkG , hQYGjJg GLJeGYjkG , hPdc dEYGOI GfOeGLg aj GdeLJeY(B. s
Crime appeared with the existence of humanity, and until the present day, crime has not ended in any civilization or society on the face of the earth, so the punishment arose because it was linked to the criminal phenomenon, whose existence was linked to the existence of the human society itself. Break the rules of social behavior. Since ancient times, punishment has taken different forms, which have evolved with the development of the human group, the development of the meaning of authority in the group, as well as the development of the religious perspective in society, and the transition of societies from the stage of agriculture to the stage of industry. In punishment, which is considered the beginning of the real emergence of the idea of punishment in modern times. Due to the fact that legal thought is of a developed and renewable nature that keeps pace with human developments from one time to another, liberty-depriving penalties appeared, and then prisons were established not only as a place to implement those penalties, but to translate the philosophy, goals, and function of punishment into a tangible implementation reality through the application of reform programs Rehabilitation is represented in refining the behavior of the offender, educating him professionally, religiously, rehabilitating him psychologically, and caring for him socially, in order to reintegrate him into society.
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI(B-(3cdjI GdMbhb(B-(3bSe GdbGfhf GdLfGFj, (B2023s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B275-292.s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdLfGFjs; (3GdJCgjd hGdEUdGM s; (3GdQOY GdYGe hGdNGUs; (3GdYbhHGJ GdSGdHI ddMQjIs; (3YbhHI GdNOeI GdeLJeYjIs; (3GdCYPGQ GdeNaaIs; (3GdeMche Ydjgs; (3GdYOGdIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs